Growth-climate relationship of Pinus wallichiana in three different parts of the Himalayas - Bhandari, S.; Speer, J. H. (Banko Janakari, 2020)
We have used six tree-ring width chronologies of Pinus wallichiana from the Himalayan region, which are available in the International Tree-Ring Data Bank (ITRDB), to determine their growth trends through time and the growth-climate relationship. Each of the chronologies downloaded from the ITRDB was detrended using an Age-dependent Cubic Smoothing Spline with a 20-year starting spline stiffness in the RCSigfree Software Program. We broke the six chronologies into three regions based on natural breaks between the sample sites. Altogether, three composite chronologies were made, one each from Bhutan, Nepal, and Pakistan. The average value for common periods was taken from each of those two chronologies to make a composite chronology. Across the three regions, the growth was lowest in the 1810s and has increased since 1980s. The growth showed a significant positive response to the winter temperature (November-February) in the eastern Himalayas in Bhutan. The chronology from Nepal showed that the growth of this species had a significant positive response to the self-calibrated Palmer Drought Severity Index of the previous year’s December and the current year’s January and March. In the western Himalayas of Pakistan, the growth of the same species is positively correlated to the annual self-calibrated Palmer Drought Severity Index. Winter temperature limits the growth of this species in the eastern Himalayas where there is enough moisture whereas the growth of this species is primarily limited by moisture in the western Himalayas